Donor-Related Risk Factors for Graft Decompensation Following Descemet's Stripping Automated Endothelial Keratoplasty - Nishisako, Sota; Yamaguchi, Takefumi; Hirayama, Masatoshi; Higa, Kazunari; Aoki, Dai; Sasaki, Chiaki; Noma, Hisashi; Shimazaki, Jun (Frontiers in Medicine, 2022)
Aims To identify donor-related risk factors associated with graft endothelial failure and postoperative endothelial cell density (ECD) reduction after Descemet's stripping automated endothelial keratoplasty (DSAEK). Methods This was a single-center retrospective study conducted from July 2006-December 2016. We included 584 consecutive eyes (482 patients) that underwent DSAEK for the treatment of laser iridotomy-related bullous keratopathy (192 eyes), pseudophakic bullous keratopathy (137 eyes), regraft (96 eyes), Fuchs' endothelial corneal dystrophy (FECD; 59 eyes) and others (100 eyes). Twenty-three donor- and recipient-related risk factors potentially associated with graft failure and ECD reduction were assessed using Cox hazard models and linear mixed effect models. Results The median age of the patients was 73.5 years (male; 35.6%). After DSAEK, ECD decreased from 2,674 cells/mm2 (95% confidence interval [CI]; 2,646–2,701) to 1,132 (1,076–1,190) at 12 months and 904 (845–963) at 24 months (P < 0.001). Fifty-five eyes (9.4%) had graft endothelial failure without rejection. This failure was associated with donor pseudophakic lens status (hazard ratio [HR]; 2.67, CI; 1.50–4.76, P = 0.001) and preoperative endothelial folds (HR; 2.82, CI; 1.20–6.62, P = 0.02). The incidence of graft endothelial failure in non-FECD patients was significantly higher among those receiving donor grafts with a pseudophakic lens status and preoperative presence of endothelial folds (P < 0.001). Postoperative ECD loss was significantly greater in eyes with these risk factors compared to those without (P = 0.007). Conclusions Pseudophakic status and/or presence of preoperative endothelial folds are the significant donor risk factors for endothelial failure in non-FECD patients.